Development Analysis Ability Profession Towards the Cultivation of Moral Ethics Based on Islamic Values at Muhammadiyah 57 Middle School Medan - Tsania, Ulfa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Instilling moral ethics based on Islamic values is a crucial aspect in the formation of student character in the educational environment, especially at SMP Muhammadiyah 57 Medan. This study aims to analyze the development of teacher professional abilities in instilling Islamic moral ethics values in the school. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the development of teacher professional abilities greatly influences the effectiveness of instilling Islamic moral values in students. Teachers who have a deep understanding of Islamic values and good pedagogical skills are able to integrate moral education into the curriculum more effectively. In addition, support from the school and a conducive environment also play an important role in this process. Challenges were also found such as the lack of special training for teachers in this field and differences in the level of understanding of moral ethics among students. This study suggests improving training programs for teachers, as well as strengthening cooperation between schools, families, and communities in instilling Islamic values holistically. Thus, it is hoped that a generation will be created that is not only academically intelligent, but also has high morals in accordance with Islamic teachings.